Preparation method applied to compact Cu-P-Sn alloy layer on steel surface
Through cold spraying and heating brazing technology, a dense Cu-P-Sn alloy layer is formed on the steel surface, and wear-resistant particles are introduced and hydrophobic surfaces are constructed, which solves the problem of insufficient thickness and performance of the copper alloy layer on the steel surface in the prior art in the prior art. , significantly improves corrosion resistance and wear resistance, and is suitable for high-demand mechanical equipment.
Patent Information
- Application Number
- CN202411296646.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-14
AI Technical Summary
In the prior art, the thickness of the steel surface copper alloy layer is low, making it difficult to ensure corrosion resistance and wear resistance, and is not suitable for high-demand use environments.
The Cu-P-Sn-based brazing material is pre-installed on the surface of the steel substrate by cold spraying, and a dense Cu-P-Sn alloy layer is formed by heating brazing, and wear-resistant particles such as tungsten carbide are introduced to improve wear-resistant performance. Hydrophobic surfaces are constructed by secondary shot peening to enhance corrosion resistance.
A uniform and dense Cu-P-Sn alloy layer closely bonded to the steel matrix is formed, which significantly improves corrosion resistance and wear resistance, and the bonding strength reaches 220MPa to 250MPa, which is suitable for high-demand mechanical equipment.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel surface treatment, in particular to a method for preparing a dense Cu-P-Sn alloy layer applied to a steel surface. Background Art
[0002] High-strength and ultra-wear-resistant copper alloys are limited by defects such as low melting point and low comprehensive mechanical properties. Cast copper alloys cannot meet the requirements of mechanical equipment to a certain extent; steel-copper composite alloys have the problem that copper alloys have weak wear resistance and can only be used for ordinary mechanical parts, and are not suitable for use environments with high requirements for wear resistance. There are many methods for preparing copper alloy composite coatings on metal surfaces. For example, CN101805903B discloses a method for laser brazing and cladding a copper alloy layer on a steel substrate. The laser machine uses argon powder feeding + laser brazing cladding + vacuum heat treatment to laser braze and clad the copper alloy layer on the steel substrate surface. The laser machine is used to remelt and solidify the steel substrate surface first. The laser beam is irradiated in all directions according to the trajectory curve of the circular steel set by a computer program, so that the copper-based alloy mixed powder is melted and solidified on the steel substrate surface to form a copper alloy layer. The copper alloy layer is 0.5 mm thick and has an average microhardness of 375 HV, which is twice that of the steel substrate. The metallographic structure of the solid solution layer is tight and firm and not easy to fall off. However, the alloy layer prepared by the invention patent CN101805903B is relatively thin, and it is difficult to guarantee the corrosion resistance and wear resistance. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a dense Cu-P-Sn alloy layer on a steel surface. The present invention pre-places a Cu-P-Sn-based brazing filler metal on the surface of a steel substrate by cold spraying and adopts a furnace heating brazing method to obtain a dense Cu-P-Sn alloy layer on the steel surface, thereby effectively improving the anti-corrosion performance.
[0004] To solve this technical problem, the technical solution of the present invention is: a method for preparing a dense Cu-P-Sn alloy layer on a steel surface, comprising the following steps: S1. One-time sandblasting treatment of the steel substrate surface to remove the oxide film on the steel substrate surface; S2, pure Cu powder, Cu3P eutectic powder and Sn powder are supersonic cold sprayed on the surface of the steel substrate to obtain a pre-deposited layer; The mass fractions of Cu powder, Cu3P eutectic powder and Sn powder in the pre-deposited layer are as follows: 35 to 40 parts of pure Cu powder; 5 to 8 parts of Cu3P eutectic powder; Sn powder 2 to 4 parts; S3. The steel substrate with the preset layer is placed in a heating furnace for brazing to obtain a Cu-P-Sn alloy layer with a tight structure to the steel substrate.
[0005] Preferably, the pre-deposited layer of S2 also includes wear-resistant particles, and the wear-resistant particles include tungsten carbide. The present invention introduces wear-resistant particles into the Cu-P-Sn alloy layer, and introduces wear-resistant particles into the low-melting-point Cu-P-Sn alloy layer in a soft-hard combination manner to improve the wear resistance of the resulting alloy layer.
[0006] Preferably, the mass of the wear-resistant particles is M1, and the total mass of the Cu powder, Cu3P eutectic powder and Sn powder is M2; M1 and M2 meet the following conditions: M1≥M2.
[0007] The Cu-P-Sn alloy layer of the present invention needs to have sufficient wear-resistant particles dispersed therein so as to improve the wear resistance of the obtained alloy layer.
[0008] Preferably, the tungsten carbide is added in the form of WC-Co composite powder, and the mass ratio of WC to Co is (8.5 to 9.5): 1; The particle size of the WC-Co composite powder is 80nm to 400nm.
[0009] The process parameters of the first sandblasting treatment in S1 are preferably as follows: The grain size of corundum used for sandblasting is 200 to 230 mesh; The distance between the spray gun muzzle and the steel substrate surface is 50 mm to 150 mm; The inclination angle between the spray gun muzzle and the surface of the steel substrate is 30° to 60°.
[0010] The present invention effectively removes the oxide film on the surface of the steel substrate through a single sandblasting process in S1, exposing Fe in the steel substrate suitable for alloy infiltration and solid solution, and roughens the surface suitable for attachment of the preset layer, and forms a tight bond between the Cu-P-Sn alloy layer and the steel substrate with the subsequent brazing process.
[0011] The process parameters of supersonic cold spraying in step S2 are preferably as follows: The working pressure of supersonic compressed gas is 0.6MPa to 0.8Mpa; Powder feeding rate 15g / min to 25g / min; Spray distance 15mm to 30mm; Spray angle 20° to 30°.
[0012] Preferably, the brazing temperature in step S3 is 695° C. to 705° C., and the brazing time is 8 min to 15 min.
[0013] Preferably, the thickness of the Cu-P-Sn alloy layer is 1 mm to 10 mm. Since the Cu-P-Sn alloy layer in the present invention is a pre-layer obtained by cold spraying and pre-pre-prepared on the surface of the steel substrate in a stable bonding manner, the thickness of the Cu-P-Sn alloy layer can be adjusted according to the actual corrosion resistance or wear resistance requirements.
[0014] Preferably, the pre-deposited layer obtained by S2 is subjected to secondary shot peening to construct a rough hydrophobic surface before brazing in step S3. The shot material used for the secondary shot peening in the present invention is iron shot material or stainless steel shot material. The present invention utilizes secondary shot peening to act on the surface of the pre-deposited layer. During the secondary shot peening process, the softer pure copper powder and the harder wear-resistant particles in the pre-deposited layer undergo asynchronous deformation. The softer copper powder undergoes a larger deformation, while the harder wear-resistant particles do not deform. The surface of the wear-resistant particle alloy layer forms a micro-nano structure surface with a hydrophobic effect due to the secondary shot peening impact, and the inner protrusion forms a depression. The preferred process parameters for constructing a hydrophobic surface with secondary shot peening are as follows: The air flow pressure is 1 / 2 of the air flow pressure of a sandblasting operation.
[0015] By adopting the above technical solution, the beneficial effects of the present invention are: The present invention uses a cold spraying method to pre-place pure Cu powder, Cu3P eutectic powder and Sn powder according to a certain mass fraction on the surface of a steel substrate after sandblasting to remove the oxide film. The pure Cu powder, Cu3P eutectic powder and Sn powder are densely accumulated on the surface of the steel substrate to effectively cover the surface of the steel substrate. With the layer-by-layer dense stacking of cold spraying, the pure copper powder effectively disperses the Cu3P eutectic powder and Sn powder in the pre-placed layer. In the subsequent heating brazing process, the copper powder melts and wets and dissolves well with Fe in the steel substrate. The Cu3P eutectic powder dispersed by the pure copper powder forms a low-temperature eutectic. At the same time, the P element can also play the role of a self-brazing agent in the process of brazing copper. P reduces copper oxide to form P in the brazing process. 2O5, the resulting reduction product P2O5 forms a composite compound with copper oxide, which is in liquid form and covers the surface of the base material at the brazing temperature, thereby preventing the base material from being oxidized. At the same time, the Sn powder dispersed in the pre-deposited layer further cooperates to lower the melting point of the Cu-P-Sn alloy, thereby obtaining a Cu-P-Sn alloy layer that is uniformly and densely covered on the steel substrate and tightly combined with the steel substrate, thereby effectively improving the corrosion resistance of the obtained steel substrate. Moreover, since the pre-deposited layer is disposed on the steel substrate by cold spraying, it is difficult to ensure the density of the obtained alloy layer and to obtain a thicker thickness, compared with the prior art in which the Cu-P-Sn alloy layer is disposed on the surface of the steel substrate by chemical plating, thereby limiting the use of the copper-based alloy layer. DETAILED DESCRIPTION
[0016] In order to further explain the technical solution of the present invention, the present invention is described in detail below through specific embodiments.
[0017] Example 1
[0018] This embodiment discloses a method for preparing a dense Cu-P-Sn alloy layer on a steel surface, comprising the following steps: S1. One-time sandblasting treatment of the Q345 steel substrate surface to remove the oxide film on the steel substrate surface; The process parameters of the first sandblasting treatment in S1 are shown in Table 2.
[0019] S2, pure Cu powder, Cu3P eutectic powder and Sn powder are supersonic cold sprayed on the surface of the steel substrate to obtain a pre-deposited layer; The mass fractions of Cu powder, Cu3P eutectic powder and Sn powder in the pre-deposited layer are shown in Table 1: The process parameters of supersonic cold spraying in step S2 are shown in Table 2.
[0020] S3. The steel substrate with the preset layer is placed in a heating furnace for brazing to obtain a Cu-P-Sn alloy layer with a tight structure to the steel substrate.
[0021] The brazing temperature and brazing time in step S3 are shown in Table 2.
[0022] The thickness of the Cu-P-Sn alloy layer is shown in Table 2.
[0023] Example 2
[0024] This embodiment discloses a method for preparing a dense Cu-P-Sn alloy layer on a steel surface, comprising the following steps: S1. One-time sandblasting treatment of the Q345 steel substrate surface to remove the oxide film on the steel substrate surface; The process parameters of the first sandblasting process in S1 are shown in Table 1. S2, pure Cu powder, Cu3P eutectic powder and Sn powder are supersonic cold sprayed on the surface of the steel substrate to obtain a pre-deposited layer; The mass fractions of Cu powder, Cu3P eutectic powder, Sn powder and WC-Co composite powder in the pre-deposited layer are shown in Table 1.
[0025] The mass of the WC-Co composite powder as wear-resistant particles is M1, and the total mass of the Cu powder, Cu3P eutectic powder and Sn powder is M2; M1 and M2 satisfy the following condition: M1≥M2.
[0026] The mass ratio of WC and Co in the WC-Co composite powder is shown in Table 1; The particle size of the WC-Co composite powder is 80nm to 400nm.
[0027] The process parameters of supersonic cold spraying in step S2 are shown in Table 2.
[0028] The pre-deposited layer obtained in step S2 is subjected to secondary shot peening to construct a rough hydrophobic surface before brazing in step S3.
[0029] The process parameters for secondary shot peening to construct a hydrophobic surface are shown in Table 2.
[0030] The air flow pressure is 0.30MPa and the sandblasting particle size is 120 mesh.
[0031] S3. The steel substrate with the preset layer is placed in a heating furnace for brazing to obtain a Cu-P-Sn alloy layer with a tight structure to the steel substrate.
[0032] The brazing temperature and brazing time in step S3 are shown in Table 2.
[0033] The thickness of the Cu-P-Sn alloy layer is shown in Table 1.
[0034] Example 3
[0035] The main differences between this embodiment and embodiment 2 are shown in Table 1 and Table 2.
[0036] Example 4
[0037] The main differences between this embodiment and embodiment 2 are shown in Table 1 and Table 2.
[0038] Comparative Example This comparative example discloses a method for preparing a Cu-P-Sn alloy layer on the surface of a steel sheet by chemical plating. The composition of the plating solution and the process conditions are as follows: CuSO4·5H2O 9g / L; SnSO4 0.9 g / L; NaH2PO2·H2O 30g / L; Complexing agent: ethylene glycol diethyl ether diamine tetraacetic acid 22g / L; Stabilizer hydroquinone 10g / L; Chemical plating temperature 55°C; The plating solution pH is 4.0 to 5.5; The thickness of the obtained Cu-P-Sn alloy layer was 25 μm.
[0039] The porosity, hardness, contact angle, electrochemical reaction resistance and brazing coating bonding interface strength after heating brazing of the Cu-P-Sn alloy layer obtained in Examples 1 to 4 and the comparative example are shown in Table 3. The test and acquisition method of the electrochemical reaction resistance is as follows: A three-electrode system was used, with the steel / Cu-P-Sn alloy layer obtained in Examples 1 to 4 and the comparative example as the working electrode, the reference electrode as a saturated calomel electrode, and the auxiliary electrode as a platinum electrode. The working electrode was placed in a 0.25% NaCl solution, and the area of the working electrode was 1 cm 2, and the rest are sealed with epoxy resin; the electrochemical impedance spectrum is tested, and the electrochemical reaction resistance is obtained by fitting with ZSimpWin software.
[0040] Table 1 Pre-layer components and amounts of Examples 1 to 4 (parts by mass)
[0041] Table 2 Process parameters for preparing Cu-P-Sn alloy layer in Examples 1 to 4
[0042] Table 3 Performance indicators of the Cu-P-Sn alloy layers obtained in Examples 1 to 4 and Comparative Examples
[0043] Combining Table 1, Table 2 and Table 3, it can be seen that compared with the comparative example, in Examples 1 to 4, the present invention uses cold spraying to pre-place pure Cu powder, Cu3P eutectic powder and Sn powder according to a certain mass fraction on the surface of the steel substrate after sandblasting to remove the oxide film. The pure Cu powder, Cu3P eutectic powder and Sn powder are tightly accumulated on the surface of the steel substrate to effectively cover the surface of the steel substrate. With the dense stacking layer by layer of cold spraying, the pure copper powder effectively disperses the Cu3P eutectic powder and Sn powder in the pre-set layer. In the subsequent heating brazing process, the copper powder melts and wets well with the Fe in the steel substrate and dissolves, and the Cu3P eutectic powder dispersed by the pure copper powder forms a low-temperature eutectic. At the same time, the P element can also play the role of a self-brazing agent in the process of brazing copper. During the brazing process, P reduces copper oxide to form P2O5. The resulting reduction product P2O5 forms a composite compound with copper oxide, which is in liquid form and covers the surface of the base material at the brazing temperature to prevent the base material from being oxidized. At the same time, the Sn powder dispersed in the pre-deposited layer further cooperates to lower the melting point of the Cu-P-Sn alloy, thereby obtaining a Cu-P-Sn alloy layer that is uniformly and densely covered on the steel substrate and tightly bonded to the steel substrate. Compared with the bonding strength of about 20 MPa between the alloy layer obtained in the comparative example and the steel substrate, the bonding strength of the alloy layer obtained in the present invention and the steel substrate is about 220 MPa to 250 MPa, that is, the alloy layer obtained in the present invention is firmly bonded to the steel substrate, and the dense alloy layer effectively improves the corrosion resistance of the obtained steel substrate. Further comparing Example 1 with Examples 2 to 4, Examples 2 to 4 utilize secondary shot peening to act on the surface of the pre-set layer. Under the action of secondary shot peening, the softer pure copper powder and the harder wear-resistant particles in the pre-set layer undergo asynchronous deformation. The softer copper powder undergoes a larger deformation, while the harder wear-resistant particles hardly deform and thus protrude from the recessed surface formed by the secondary shot peening impact. The alloy layer forms a hydrophobic micro-nano structure, which reduces the spreading of water or aqueous solution on the surface of the alloy layer, effectively alleviating the direct contact between water or aqueous corrosive solution and the surface of the alloy layer, greatly reducing the actual contact area, and improving its corrosion resistance.
Claims
1. A method for preparing a dense Cu-P-Sn alloy layer on a steel surface, characterized in that: The following steps are involved: S1. One-time sandblasting treatment of the steel substrate surface to remove the oxide film on the steel substrate surface; S2, pure Cu powder, Cu3P eutectic powder and Sn powder are supersonic cold sprayed on the surface of the steel substrate to obtain a pre-deposited layer; The mass fractions of Cu powder, Cu3P eutectic powder and Sn powder in the pre-deposited layer are as follows: 35 to 40 parts of pure Cu powder; 5 to 8 parts of Cu3P eutectic powder; Sn powder 2 to 4 parts; S3. The steel substrate with the preset layer is placed in a heating furnace for brazing to obtain a Cu-P-Sn alloy layer with a tight structure to the steel substrate.
2. The method for preparing a dense Cu-P-Sn alloy layer on a steel surface as claimed in claim 1, characterized in that: The pre-deposited layer of S2 also includes wear-resistant particles, and the wear-resistant particles include tungsten carbide.
3. The method for preparing a dense Cu-P-Sn alloy layer on a steel surface as claimed in claim 2, characterized in that: The mass of the wear-resistant particles is M1, and the total mass of the Cu powder, Cu3P eutectic powder and Sn powder is M2; M1 and M2 meet the following conditions: M1≥M2.
4. The method for preparing a dense Cu-P-Sn alloy layer on a steel surface as claimed in claim 2, characterized in that: The tungsten carbide is added in the form of WC-Co composite powder, and the mass ratio of WC to Co is (8.5 to 9.5): 1; The particle size of the WC-Co composite powder is 80nm to 400nm.
5. The method for preparing a dense Cu-P-Sn alloy layer on a steel surface according to claim 1, characterized in that: The process parameters of the first sandblasting process in S1 are as follows: The grain size of corundum used for sandblasting is 200 to 230 mesh; The distance between the spray gun muzzle and the steel substrate surface is 50 mm to 150 mm; The inclination angle between the spray gun muzzle and the surface of the steel substrate is 30° to 60°.
6. The method for preparing a dense Cu-P-Sn alloy layer on a steel surface according to claim 1, characterized in that: The process parameters of supersonic cold spraying in step S2 are as follows: The working pressure of supersonic compressed gas is 0.6MPa to 0.8Mpa; Powder feeding rate 15g / min to 25g / min; Spray distance 15mm to 30mm; Spray angle 20° to 30°.
7. The method for preparing a dense Cu-P-Sn alloy layer on a steel surface as claimed in claim 1, characterized in that: The brazing temperature in step S3 is 695° C. to 705° C.; the brazing time is 8 min to 15 min.
8. The method for preparing a dense Cu-P-Sn alloy layer on a steel surface as claimed in claim 1, characterized in that: The thickness of the Cu-P-Sn alloy layer is 1 mm to 10 mm.
9. A method for preparing a dense Cu-P-Sn alloy layer on a steel surface as claimed in any one of claims 1 to 8, characterized in that: The pre-deposited layer obtained in step S2 is subjected to secondary shot peening to construct a rough hydrophobic surface before brazing in step S3.
10. The method for preparing a dense Cu-P-Sn alloy layer on a steel surface according to claim 1, characterized in that: The process parameters for secondary shot peening to construct a hydrophobic surface are as follows: The air flow pressure is 1 / 2 of the air flow pressure of a sandblasting operation.
Citation Information
Patent Citations
Method for cladding copper alloy layer on surface of steel substrate by laser brazing
CN101805903B